Biosorption of Chlorothalonil on Fique’s Bagasse (Furcraea sp.): Equilibrium and Kinetic Studies (2010)
The bagasse generated as residue during the process of fiber extraction of the fique or sisal (Furcraea sp.) has been evaluated in raw state, washed and thermally activated for the adsorption of chlorothalonil (CLT). The studywas developed at 25 ℃the effects of contact times, biomass dose and pH were investigated. The bagasse was characterized using Scanning Electronic Microscopy (SEM) and Fourier Transform Infrared Spectroscopy (FTIR). A significant change in the signal spectroscopics was found in the thermally activated material. The experimental data obtained in this study shows that the fique’s bagasse is a material with potential to be used in adsorption of pollutants. The maximum uptake was 57.143 mg/g for the thermally activated material. This outcome constitutes a good contribution in environmental and technical terms.